PSYCHO-SOCIAL SUPPORTS AND FAMILY INTEGRATION AS DETERMINANTS OF PALLIATIVE CARE OF TERMINALLY-ILL PATIENTS IN UNIVERSITY COLLEGE HOSPITAL, IBADAN NIGERIA (2015)
Orthodox medical practice has brought about access to diagnosis and modern healthcare through the palliative care system to treat the terminally-ill, thereby improving their quality of life. This treatment of the terminally-ill utilises medical diagnostic interventions with little or no consideration for psychosocial supports and family integration which are at the core of the palliative care system. This study, therefore, investigated the psychosocial supports (diversional, behavioural, emotional, counselling services, companionship, spirituality, rehabilitative supports and regular visitation) and family integration (financial assistance, life-style modification and re-allocation of roles) as determinants of palliative care of terminally-ill patients at University College Hospital, (UCH), Ibadan, Nigeria. The study adopted the survey research design. The UCH was purposively selected. Proportionate and stratified random sampling techniques were used to select 587 respondents, namely, 183 health workers (50 doctors, 83 nurses, 24 physiotherapists and 26 social workers), 202 terminally-ill patients and 202 family caregivers from purposively selected eight wards and three out-patient clinics. Three instruments were used: Psychosocial Support Scale (r=0.67), Family Integration Scale (r=0.65) and Palliative Care Services Scale (r=0.71). These were complemented with ten sessions of in depth interview with the health workers, terminally-ill patients and family caregivers. Two research questions were answered and three hypotheses tested at 0.05 level of significance. Data were analysed using descriptive statistics, Pearson product moment correlation, multiple regression and content analyses. The respondents were 218 male, and 369 female with age of 38.54, ±SD=9.78; with 202 terminally-ill patients; cancer (86), cardiac problems (42), neurological disorders (33), end stage kidney problems (22) and HIV/AIDS (19). Psychosocial supports and family integration significantly correlated with palliative care of the terminally-ill (F(12.189)= 25.25, R=.79); and jointly accounted for 62.0% of the variance in their palliative care. Psychosocial supports (β = .55) and family integration (β= .51) relatively contributed to the palliative care system. Components of psychological supports had significant positive relationship with palliative care as follows: emotional support (r=.69), diversional support (r=.54), behavioural support (r=.50) and counseling services (r=.45). Also, components of social supports had positive relationship with palliative care: regular visitation (r=.41), spirituality (r= .33), rehabilitative support (r= .308) and companionship (r= .066). Observed relationship among family integration factors and palliative care were: financial assistance (r=.65), life-style modification (r=.32) and reallocation of roles (r=.32). Problems facing the utilisation of palliative care system include: irregular training on palliative care for health workers (64.0%), problem of early diagnosis (62.0%), non-availability of pain control medication (58.2%) and non-affordability of treatment (23.0%). Patients expressed anxiety over the outcome of illness, difficulty in adaptation to life style modification and fear of death in the face of poor patient-health workers communication. Psychosocial support and family integration positively influenced palliative care system for the terminally-ill patients at the University College Hospital, Ibadan, Nigeria. Therefore, adequate provision of funds, pain control medication and staff retraining are required to ensure effective treatment in palliative care. In addition, the terminally-ills and their family members should be appropriately counselled on the need for life-style modifications and role reallocation.